Pemanfaatan IoT (Internet of Things) Pada Irigasi Tetes Untuk Tanaman Jeruk - Mila Kusumawardani Kusumawardani; Moechammad Sarosa; Ratih Indri Hapsari (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Citrus X sinensis plants are one of the main products of Petungsewu Village, Malang Regency. So far, partners (citrus farmers) have relied on rainwater by using rainfed systems to irrigate their crops. Problems arise during dry season because limited water making watering or spraying become difficult. As a result plants are only able to produce fruits once a year while the same plants in other lands with good irrigation can produce fruits twice. To overcome the problem of limited water, it is determined to have a 4x6x2 m3 water reservoir as an water storage area for rainfed systems. While to control water usage when watering uses a cliff system using the Internet of Things (IoT) technology. In addition, to provide water storage, this activity also built a shelter on the reservoir and toilets. Because of the unavailability of electrical energy sources, this activity also provides renewable energy sources that contain solar panel energy. The watering system is carried out automatically using a soil moisture sensor if the humidity is less than 70%, so that the valve will open and the water flows. On the other hand, if the humidity is greater or equal to 70%, the valve will be closed. With the existence of this activity, partners can do automatic watering of plants during dry season, and citrus plants can produce fruits twice in a year